Stakeholders - Robert Gorwa (Yale Law School, 2022)
When we talk about platforms and processes of platform governance, who exactly are we talking about? This essay, published in the Yale ISP-WIII Platform Governance Terminologies series, provides a typology and discussion of the various global actors that are potentially a part of the platform governance ecosystem.
Keywords: 330; content moderation; digital politics; platform governance